Thermodynamical and electronic properties of BxAl1−xN alloys: A first principle study. (November 2015) - Kumar, S.; Joshi, Suman; Joshi, B.; Auluck, S.
Abstract: A series of first principle calculations were carried out to investigate thermodynamical, electronic and optical properties of cubic B x Al 1 − x N ordered alloys using supercell approach within density functional theory (DFT). Here we calculate the lattice constants using van der Waals density functional (vdW-DF) at several concentrations ( x ) of boron. We find that the vdW-DF prediction shows slightly better agreement with experiment in contrast to local density approximation (LDA)/generalized gradient approximation (GGA). The results show that the direct energy band gap (Γ v –Γ c ) has strong nonlinear dependence on the concentration ( x ). At x =0.04 and 0.84, B x Al 1 − x N has a phase transition from direct to an indirect band gap semiconductor. To describe the alloys' solubility, formation enthalpy were calculated and fitted to quadratic function to obtain interaction parameter. The calculated T – x phase diagram shows a broad miscibility gap with a high critical temperature equal to 3063 K. The calculated dielectric function is explained in terms of band structure and density of states and compared with the available experimental data, showing good agreement. Abstract : Highlights: We have performed Geometry optimization for B x Al 1 − x N alloys. Formation enthalpy and miscibility gap are predicted for alloys. The calculated band structure shows the zone folding. Total and partial density of states are calculated for alloys. The imaginary part of dielectric function are also calculated.